Molecular nature of two beta-lactamase-specifying plasmids isolated from Haemophilus influenzae type b. - De Graaff, J (1976)
The molecular nature of two beta-lactamase-specifying plasmids isolated from two separate ampicillin-resistant Haemophilus influenzae type b strains was examined. A 30 X 10(6)-dalton (30-Mdal) plasmid (RSF007) had a copy number of approximately 3 per chromosomal equivalent and a mole fraction guanine plus cytosine content of 0.39. By heteroduplex analysis the 30-Mdal plasmid was found to contain the entire ampicillin translocation DNA segment (TnA) found on R factors of enteric origin. A 3.0-Mdal plasmid (RSF0885) was found as a multicopy pool of approximately 28 copies per chromosomal equivalent, had a mole fraction guanine plus cytosine content of 0.40, and contained only about one-third of the transposable TnA sequence. RSF007 and RSF0885 appeared to be unrelated plasmids in that they share base sequence homology only within the confines of the TnA segment. The 3.0-Mdal Haemophilus plasmid was used to transform E. coli to ampicillin resistance but was found to be unstable in this host in the absence of antibiotic. The possibility that R-plasmids arose in Haemophilus by the translocation of TnA from a donor R-factor onto an indigenous H. influenzae plasmid is discussed.